Promoting Sustainable Life Through Global Citizenship-Oriented Educational Approaches: Comparison of Learn-Think-Act Approach-Based and Lecture-Based SDG Instructions on the Development of Students' Sustainability Consciousness - Koculu, Asli (MDPI, 2025)
Promoting individuals' sustainability consciousness (SC) is one of the important way of ensuring a sustainable world and finding ways toward a better life. Therefore, the purpose of the present study was to compare the effects of learn-think-act approach-based instruction and lecture-based instruction on the development of sustainability consciousness in students, with the Sustainable Development Goals (SDGs) acting as the subject of the instructions. The research was conducted with 80 seventh-grade students from a state school in Istanbul, T & uuml;rkiye. While 40 of them were in a class where learn-think-act approach-based SDG instruction was implemented, the other 40 participants were trained with lecture-based SDG instruction for eight weeks. A quasi-experimental research design was followed in the research. The data was collected with the Sustainability Consciousness Questionnaire and obtained before and after SDG instruction. In the data analysis, paired and independent samples t-tests were used. The findings revealed that learn-think-act approach-based SDG instruction has a significantly larger effect (d = 1.62, 95% CI) on the development of sustainability consciousness in middle school students compared to lecture-based SDG instruction.
Keywords: sustainable life; global citizenship-oriented educational approach; sustainable development goals (SDGs); sustainability consciousness; learn-think-act approach-based instruction; lecture-based instruction; middle school students; PRESERVICE TEACHERS; IMPACT; ACHIEVEMENT; Science & Technology - Other Topics; Environmental Sciences & Ecology